Respon Peternak Domba Terhadap Aplikasi Teknologi Pakan dan Hormon Reproduksi - Muhammad Matin Muta'Ali; Ulfa Indah Laela Rahmah Rahmah; Lili Adam Yuliandri (Tropical Livestock Science Journal, 2023)
This research was carried out from May to June 2021, and is located in the Majalengka Regency, West Java Province, which is located at the coordinates of 6°48'50.0"S 108°13'35.8" and is at an altitude of 141 m above sea level (Bappeda). The purpose of this study was to analyze the response of sheep breeders to the application of feed technology and reproductive hormones. The object of this research is the sheep breeder in the District of Jati Tujuh, Majalengka Regency. This research was conducted by survey using the quantitative descriptive method, determining the research area using the purposive sampling method. Determination of the number of respondents was calculated using the Slovin formula with a confidence level of 90% (r = 0.1) with the results of the calculation amounting to 85 people. The variables measured were Characteristics (Age, Business Scale Level, Livelihood Level, Last Education, Livestock Experience) and Response (Cognitive, Affective, Psychomotor). Data processing in this study used the Kendall Tau Correlation Test Analysis. The results showed that the response of sheep breeders to the Application of Feed Technology and Reproductive Hormones in Jati Tujuh District was in the very weak category, it was because most of the breeders were over 50 years of age with a low level of education, namely elementary school graduates, so that farmers found it difficult to implement and understand information. regarding livestock technology. The data shows that the level of characteristics significantly affects the response of farmers. The results of the study also show that the relationship between the characteristics of the response is in the very weak category or has no significant effect. It can be concluded that the characteristics have a significant effect on the response of farmers. The better the level of characteristics, the better the effect on the response. The relationship between the two variables between the characteristics and the response is in the very weak category.